Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2470730
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing crowd workers in mobile pay-for-answer q&a

Abstract: Despite the popularity of mobile pay-for-answer Q&A services, little is known about the people who answer questions on these services. In this paper we examine 18.8 million question and answer pairs from Jisiklog, the largest mobile payforanswer Q&A service in Korea, and the results of a complementary survey study of 245 Jisiklog workers. The data are used to investigate key motivators of participation, working strategies of experienced users, and longitudinal interaction dynamics. We find that answerers are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
2
24
0
Order By: Relevance
“…Answers, Quora) was free and open to the public. Recently, these service providers have recognized the business value of social Q&A sites, and launched new business models to monetize online knowledge (Hsieh, Kraut, & Hudson, ; Lee, Kim, Yi, Sung, & Gerla, ). One of the most popular business models is the tri‐lateral payment‐based social Q&A platform (hereinafter called tri‐lateral Q&A), which has drawn growing attention from both practitioners and researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Answers, Quora) was free and open to the public. Recently, these service providers have recognized the business value of social Q&A sites, and launched new business models to monetize online knowledge (Hsieh, Kraut, & Hudson, ; Lee, Kim, Yi, Sung, & Gerla, ). One of the most popular business models is the tri‐lateral payment‐based social Q&A platform (hereinafter called tri‐lateral Q&A), which has drawn growing attention from both practitioners and researchers.…”
Section: Introductionmentioning
confidence: 99%
“…altruism is the leading factor, followed by business motives, learning, hobbies, and earning points. In pay-for-answer Q&A sites, researchers have reported that financial incentives and social factors are the key motivators [13,31,32,23]. In this work, we extend the prior studies by identifying unique motivators for local knowledge sharing.…”
Section: Conventional Social Qandamentioning
confidence: 64%
“…category refinement, question routing, and related answer searches. When compared with conventional social Q&A sites [7,23], the overall topic distribution of location-based social Q&A had a higher level of travel and lifestyle information seeking, but a lower level of computer related questions.…”
Section: Leveraging Topical/typological Patternsmentioning
confidence: 90%
“…Specifically, managers should conduct an in-depth user survey, especially for understanding their perception of pricing and reward. Previous studies have also reported that the pricing mechanism greatly influences the askers' and answerers' behaviors (Chen et al, 2010;Hsieh et al, 2010;Jeon & Rieh, 2013;Lee et al, 2013;. Based on the pertinent findings, trilateral Q&A platforms can be designed better in terms of pricing and rewarding strategies.…”
Section: Implications For Practicementioning
confidence: 96%
“…Answers, Quora, and so on) was free and open to the public. Recently, these service providers have recognized the business value of social Q&A sites, and launched new business models to monetize online knowledge (Chen, Ho, & Kim, 2010;Hsieh, Kraut, & Hudson, 2010;Lee, Kim, Yi, Sung, & Gerla, 2013). One of the most remarkable business models is the *Corresponding author Additional Supporting Information may be found in the online version of this article.…”
Section: Introductionmentioning
confidence: 99%